Management processes in distance education: analysis of the polo coordination in the Open University of Brazil system (Research, Society and Development, 2021)
This study seeks to understand the pole management processes of the Federal University of Santa Maria (UFSM), within the scope of the Open University of Brazil (UAB) considering the public policies that organize the UAB and its developments. The research was developed in the Postgraduate Program in Public Policies and Educational Management. The theoretical contribution was based on the main authors who think public policies for Distance Education (EAD) in Brazil and on the educational management processes. The UAB regulation was sought in the legal framework, looking for elements that configure the Pole Coordinator's performance in this scenario. The methodological guidelines are based on the qualitative approach, considering that the researcher is not outside the reality he studies, outside of it, of the phenomena to which he seeks to understand their meanings. Six research coordinators were defined as research subjects with active offer of the Pedagogy Course at UAB / UFSM. Data collection took place through semi-structured interviews, carried out both in person and at a distance. To analyze the data, Discursive Textual Analysis was used. Three categories emerged from the analyzes: 1st) The process of choosing the pole coordinator; 2nd) Perceptions about the pole coordinator's duties; 3rd) The difficulties experienced as a pole coordinator. At the end of the research, it was observed that a more detailed knowledge of the documents and materials describing the activities that make up his work could qualify the management of the coordinators at the pole.